Insights into high-altitude adaptation and meat quality regulation by gastrointestinal metabolites in Tibetan and black pigs - Bai, Xue; Huang, Zhiying; Tan, Helin; Gu, Yiren; Wang, Xun; Jin, Long; Shang, Peng; Long, Keren; Li, Diyan; Li, Mingzhou (Frontiers in Veterinary Science, 2025)
IntroductionTibetan pigs, native to the Qinghai-Tibet Plateau, have adapted over millennia to extreme conditions such as low oxygen, harsh cold, and high UV radiation, impacting their muscle characteristics and digestive tract microbiota. The quality of pork from Tibetan pigs (TP) and black pigs (BP) is influenced by various factors, including genetics, diet, and environmental adaptation. However, the specific influence of digestive tract microbiota metabolites on muscle traits remains poorly understood. Our goal was to correlate omic variations with meat quality traits and identify potential biomarkers predictive of superior meat quality, elucidate the regulatory effects of digestive tract microbial metabolites on Tibetan pig muscle characteristics, and reveal the genetic and nutritional mechanisms that promote adaptation to extreme environmental conditions.MethodsThis analysis encompassed metabolomic profiling of the entire digestive tract-including the stomach, jejunum, cecum, colon, and rectum-as well as histological, amino acid, fatty acid composition, and transcriptomic assessments of the longissimus dorsi muscle tissues to investigate how digestive tract microbial metabolites influence muscle adaptation to high altitudes.ResultsAnalyses revealed that Tibetan pig muscles contain smaller, more oxidative fibers enriched with flavor-enhancing amino acids. This was accompanied by a more favorable n-6/n-3 fatty acid ratio. Distinct patterns of microbial metabolites were observed in the digestive tract, influencing protein digestion and purine metabolism, and correlating with muscle glycine levels. Transcriptomic data showed varied gene expression in metabolic pathways related to salivary and pancreatic secretion, as well as carbohydrate and fatty acid metabolism. Integrated multi-omics approaches linked stomach metabolism, particularly through bile secretion pathways influenced by acetylcholine, to muscle functionality, highlighting the important role played by the ATP1B4 gene in enabling muscle physiology in Tibetan pigs.DiscussionThis study highlights the importance of targeted dietary interventions in improving meat quality for specific pig breeds. It also provides a theoretical foundation for precision agriculture strategies aimed at enhancing the meat quality of both TP and BP pigs.